Financial Education in Amazonas: Evaluating Virtual and Traditional Methods - VALLADOLID BENAVIDES, Anita Maribel; PUICAN RODRIGUEZ, Victor Hugo; VARGAS ESPINOZA, Jorge Luis; GUIVIN GUADALUPE, Alex Lenin; MALUQUIS, Eder Julca; MORI, Jhonmar Minga (Theoretical and Practical Research in Economic Fields, 2025)
This research focused on examining how digital financial education, financial innovation, digital literacy, digital finance, and globalization influence face-to-face financial education in Bagua, Peru. The aim is to contribute to the fulfillment of the Sustainable Development Goal (SDG) related to quality education. The study uses a quantitative approach, and a descriptive-explanatory non-experimental design and data collected from 304 participants using a validated questionnaire. The results showed that digital financial education faces significant barriers, mainly due to the lack of connectivity and familiarity with digital tools; however, participants showed a strong preference for face-to-face financial education, although they also expressed a willingness to integrate digital methods; the analysis of the predictor variables revealed that digital financial education and digital finance positively influence face-to-face financial education, while financial innovation and digital literacy did not show a significant influence. In conclusion, the results express the need for public policies and educational strategies that promote a hybrid model, compounding both digital and in-person learning, to improve financial inclusion in regions with technological gaps. Besides, globalization plays an important role but is not yet fully integrated into financial education.